Bedaquiline resistance in Mycobacterium tuberculosis during antimycobacterial therapy and its impact on clinical outcomes (clinical cases) - Raznatovska, О. М.; Yasinskyi, R. M.; Shalmin, O. S.; Fedorets, A. V.; Svitlytska, O. A.; Разнатовська, Олена Миколаївна; Ясінський, Роман Миколайович; Шальмін, Олександр Самуілович; Федорець, Андрій Васильович; Світлицька, Оксана Анатоліївна (Запорізький державний медичний університет, 2023)
Aim. To analyze the nature of Bedaquiline (Bdq) resistance in Mycobacterium tuberculosis (MBT) during antimycobacterial therapy (AMBT) in patients with multidrug-resistant tuberculosis (MDR-TB), its impact on clinical outcomes and to detect risk factors for the Bdq drug resistance development on the example of own observed clinical cases. Materials and methods. 2 clinical cases of own observations of the Bdq resistance development in MBT during AMBT in patients with MDR-TB who were treated at the clinical base of the Department of Phthisiology and Pulmonology of Zaporizhzhia State Medical University – Pulmonary Tuberculosis Department No. 2 of the Communal Non-profit Organization “Zaporizhzhia Regional Phthisio-Pulmonology Clinical Treatment and Diagnostic Center” are presented. Results. The presented clinical cases confirm the literature data that the treatment effectiveness in patients with Rifampicin-resistant TB (RR-TB) and MDR-TB is associated with Bdq drug resistance. Regarding the reasons for the development of acquired Bdq drug resistance, the second clinical case, like the examples of other authors, demonstrates low adherence to treatment. There is no data in the literature about the lack of controlled treatment at the outpatient stage as a risk factor for Bdq drug resistance and negative clinical outcomes in patients with MDR-TB, which would complement the scientific experience in this problem. Conclusions. In both clinical cases, Bdq drug resistance was acquired (secondary), and had an impact on the clinical outcomes of tuberculosis treatment. The risk factors for Bdq drug resistance and negative clinical outcomes were lack of controlled treatment at the outpatient stage in the first case and low adherence to treatment in the second one. Мета роботи – на прикладі клінічних випадків власного спостереження у хворих на туберкульоз з множинною лікарською стійкістю (МDR-TB) проаналізувати характер резистентності мікобактерій туберкульозу (МБТ) до бедаквіліну (Bdq) під час антимікобак- теріальної терапії (АМБТ), її вплив на клінічні наслідки та встановити фактори ризику виникнення лікарської стійкості до Bdq. Матеріали та методи. Наведено 2 клінічні випадки власного спостереження виникнення резистентності МБТ до Bdq під час АМБТ у хворих на МDR-TB, які перебували на лікуванні у відділенні легеневого туберкульозу № 2 Комунального некомерційного підприємства «Запорізький регіональний фтизіопульмонологічний клінічний лікувально-діагностичний центр» Запорізької обласної ради – клінічній базі кафедри фтизіатрії і пульмонології Запорізького державного медичного університету. Результати. Наведені клінічні випадки підтверджують відомості фахової літератури про те, що ефективність лікування хворих на МDR-TB пов’язана з лікарською стійкістю до Bdq. Щодо причин виникнення набутої лікарської стійкості до Bdq, то у другому клінічному випадку показано низьку прихильність до лікування, і на це вказують багато авторів. Про відсутність контрольованого лікування на амбулаторному етапі як фактор ризику лікарської стійкості до Bdq і негативних клінічних наслідків у хворих на МDR-TB даних у науковій літературі немає, а отже це доповнить науковий досвід із цієї проблеми. Висновки. В обох клінічних випадках лікарська стійкість до Bdq була набутою (вторинною) та впливала на клінічні наслідки лікування туберкульозу. Фактор ризику лікарської стійкості до Bdq та негативних клінічних наслідків у першому випадку – відсутність контрольованого лікування на амбулаторному етапі, у другому – низька прихильність до лікування.
Резистентність мікобактерій туберкульозу до бедаквіліну під час антимікобактеріальної терапії та її вплив на клінічні наслідки (клінічні випадки)
Raznatovska O. M. - ORCID ID: 0000-0003-2252-9063; Yasinskyi R. M. - ORCID ID: 0000-0003-4132-731X; Shalmin O. S. - ORCID ID: 0000-0002-1727-0408; Fedorets A. V. - ORCID ID: 0000-0003-0994-5265; Svitlytska O. A. - ORCID ID: 0000-0003-4987-8458.
Keywords: multidrug-resistant tuberculosis; bedaquiline; results; туберкульоз з множинною лікарською стійкістю; бедаквілін; результат